Comparison of Transforaminal Epidural Versus Intra-Articular Facet Joint Injection for Treatment of Lumbar Radiculopathy - Tariq, Haroon; Iqbal, Muhammad Rashid; Khan, Rao Ali Shan; Zaid, Ameer Yasser; Raza, Ali; Shah, Syed Aqib Ali (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the analgesic efficacy of intra-articular facet joint block versus transforaminal epidural injection in patients with lumbar radiculopathy. Study Design: Randomized controlled trial (IRCT trial id number 73631) Place and Duration of Study: Anesthesia Department, Combined Military Hospital Rawalpindi, Pakistan, from Jun to Nov 2023. Methodology: Patients were divided into two groups of 45 each, the facet-joint group (Group-A) and the epidural group (Group-B). Primary variables observed were median scores on standard visual analog scale (VAS), with 0 being no pain to 10 being excruciating pain, numeric rating scale (NRS), with 0 being no pain to 100 being excruciating pain and disability classification according to the Oswestry disability index (ODI). Results: Median pain score on visual analog scale (VAS) was 3.00 (IQR=1.00) in Group-A versus 4.00 (IQR=0.00) in Group-B on follow-up after four weeks (p=0.002). The same assessment done after 3 months between both groups showed a median VAS score of 4.00 (IQR=0.00) in Group-A versus 4.00 (IQR=0.00) in Group-B (p=1.000). Assessment on the Oswestry disability index showed median scores of 15.00 (IQR=8.00) in Group-A versus 15.00 (IQR=10.00) in Group-B after 4 weeks. Similar assessment done at 3 months showed median score of 20.00 (IQR=20.00) in Group-A versus 25.00 (IQR=18.00) in Group-B (p=0.399). Conclusion: We conclude that facet-joint injection provides adequate analgesia with better pain scores than transforaminal epidural injections for treatment of lumbar radiculopathy.